Growth Response of Mung Bean (Vigna radiata L.) to Biochar and Liquid Organic Fertilizer from Samanea saman (Jacq.) Merr Leaves Combined with Bone Meal - Tasha Mumtazah; Hafnati Rahmatan; Muhibbuddin; Samingan; Djufri (Jurnal Penelitian Pendidikan IPA, 2025)
The limited phosphorus content in liquid organic fertilizer derived from Samanea saman (Jacq.) Merr. leaves may constrain its effectiveness in promoting the growth of mung bean (Vigna radiata L.). This study aimed to improve the fertilizer's efficacy by incorporating bone meal as a phosphorus source and applying biochar to enhance nutrient retention and soil properties. A 2×5 factorial experiment was arranged in a Completely Randomized Design (CRD), with two treatment factors: biochar application (0 and 100 g per polybag) and fertilizer formulations (control, 100% S. saman leaf extract, and combinations of S. saman leaf extract with bone meal at 25%, 50%, and 75% ratios). Growth parameters observed included plant height, number of leaves, and dry weight. The combination of 50% S. saman leaf fertilizer and 50% bone meal, supplemented with biochar, produced the highest performance, with a plant height of 65.72 cm, 22.06 leaves per plant, and a dry weight of 75.82 g. In contrast, treatments without biochar exhibited significantly lower growth. These findings demonstrate that the synergistic application of bone meal and biochar can substantially enhance nutrient availability and improve the performance of organic fertilizers in supporting mung bean growth.